AKTIVITAS ANALGESIK EKSTRAK ETANOL DAUN SOYOGIK (Saurauia bracteosa DC) PADA TIKUS PUTIH JANTAN GALUR WISTAR - Legoh, Dina Imorina; Runtuwene, Max R.J.; Yamlean, Paulina V.Y. (PHARMACON, 2021)
ABSTRACT  Soyogik leaves (Saurauia bracteosa DC) are plants that have flavonoid compounds that act as analgesics. This study aims to test the analgesic activity of soyogic leaf extract on male white rats Wistar strain using the thermic pain induction method. This research method is laboratory experimental, using male white rats (Rattus novergicus). The results obtained from the number of responses of mice between before and after giving the test solution. The treatment was initiated by thermal induction of pain in rats. Furthermore, the rat response was calculated, then given negative control (CMC), positive control (paracetamol), and soyogic leaf extract with a dose of 0.375 g / KgBB, 0.75 g / KgBB and 1.5 g / KgBB. The response of the mice after being given the treatment was seen from the 30th, 60th, 90th, and 120th minutes. Data were analyzed using the SPSS program, the real differences between the treatments were tested by one way ANOVA. The results showed that soyogic leaf extract with a dose of 0.375 g / KgBB, a dose of 0.75 g / KgBB and a dose of 1.5 g / KgBB have analgesic activity. Keywords: analgesics, Saurauia bracteosa DC, Rattus norvegicus  ABSTRAK Daun soyogik (Saurauia bracteosa DC) merupakan tanaman yang memiliki senyawa flavonoid yang berperan sebagai analgesik. Penelitian ini bertujuan untuk menguji aktivitas analgesik dari ekstrak daun soyogik pada tikus putih jantan galur wistar dengan metode induksi nyeri cara termik. Metode penelitian ini adalah eksperimental laboratorium, menggunakan tikus putih jantan (Rattus novergicus). Hasil penelitian diperoleh dari jumlah respon tikus antara sebelum dan sesudah pemberian larutan uji. Perlakuan diawali dengan induksi nyeri cara termik pada tikus. Selanjutnya dihitung jumlah respon tikus, kemudian diberikan kontrol negatif (CMC), kontrol positif (paracetamol), dan ekstrak daun soyogik dosis  0,375 g/KgBB, 0,75 g/KgBB dan 1,5 g/KgBB. Respon tikus setelah diberikan perlakuan dilihat mulai dari menit ke 30, 60, 90, dan 120. Data dianalisis menggunakan program SPSS, beda nyata antar perlakuan diuji dengan one way ANOVA. Hasil yang didapat menunukkan ekstrak daun soyogik dosis 0,375 g/KgBB, dosis 0,75 g/KgBB dan dosis 1,5 g/KgBB memiliki aktivitas analgesik.  Kata Kunci: analgesik, Saurauia bracteosa DC, Rattus norvegicus